Unique challenges to control the spread of COVID-19 in the Middle East - Zulqarnain Baloch; Zhongren Ma; Yunpeng Ji; Mohsen Ghanbari; Qiuwei Pan; Waleed Aljabr (Elsevier, 2020)
The COVID-19 pandemic is spreading at unprecedented pace among the Middle East and neighboring countries. This region is geographically, economically, politically, culturally and religiously a very sensitive area, which impose unique challenges for effective control of this epidemic. These challenges include compromised healthcare systems, prolonged regional conflicts and humanitarian crises, suboptimal levels of transparency and cooperation, and frequent religious gatherings. These factors are interrelated and collectively determine the response to the pandemic in this region. Here, we in-depth emphasize these challenges and take a glimpse of possible solutions towards mitigating the spread of COVID-19.